2010
DOI: 10.1021/om900594z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations on Reactions of a Series of Stable Dialkyl-Substituted Silicon−Chalcogen Doubly Bonded Compounds

Abstract: The potential energy surfaces for the formation, addition, and cycloaddition reactions of dialkylsilanechalcogenone (2) species have been studied using three levels of theories, i.e., B3LYP/ LANL2DZdp, CCSD theory, and Gibbs free energy (at the B3LYP level). Four dialkylsilanechalcogenone species with a SidX bond, where X = O, S, Se, and Te, have been chosen as model reactants in this work. Also, both MeOH addition and isoprene cycloaddition have been used to study the chemical reactivities of these species (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Remarkably little quantitative information on the reactivity of these species exists, in spite of considerable interest over the past few decades in the chemistry of silicon-chalcogen double bonds and the synthesis of stable compounds containing these intrinsically highly reactive moieties. Several stable silacarbonyl compounds have been reported, all but one of them containing chelating ligands to stabilize the highly reactive silicon−oxygen double bond. However, a stable dialkyl- or diarylsilanone (with or without chelating ligands) has yet to be reported, and thus, most of our knowledge regarding the spectroscopic properties and structures of these compounds has been gained through low-temperature matrix isolation studies ,,, and theoretical calculations. ,, Silanethiones are thought to be more thermodynamically stable than silanones due to a lower polarity of the SiS bond, ,, and indeed two sterically stabilized, base-free silanethiones have been reported in addition to a few donor-coordinated derivatives. However, remarkably few transient silanethiones have been observed directly, either in low-temperature matrixes, the gas phase, or in solution …”
Section: Introductionmentioning
confidence: 99%
“…Remarkably little quantitative information on the reactivity of these species exists, in spite of considerable interest over the past few decades in the chemistry of silicon-chalcogen double bonds and the synthesis of stable compounds containing these intrinsically highly reactive moieties. Several stable silacarbonyl compounds have been reported, all but one of them containing chelating ligands to stabilize the highly reactive silicon−oxygen double bond. However, a stable dialkyl- or diarylsilanone (with or without chelating ligands) has yet to be reported, and thus, most of our knowledge regarding the spectroscopic properties and structures of these compounds has been gained through low-temperature matrix isolation studies ,,, and theoretical calculations. ,, Silanethiones are thought to be more thermodynamically stable than silanones due to a lower polarity of the SiS bond, ,, and indeed two sterically stabilized, base-free silanethiones have been reported in addition to a few donor-coordinated derivatives. However, remarkably few transient silanethiones have been observed directly, either in low-temperature matrixes, the gas phase, or in solution …”
Section: Introductionmentioning
confidence: 99%
“…The corresponding reaction mechanisms were studied computationally and were found to be highly exothermic displaying low reaction barriers 17. A computational study18 of the formation of SiE bonds through the reaction of the silylene15a,b with Me 3 PE showed that there is a low reaction barrier for the oxidation (E=O) of the silylene while the reaction is spontaneous and follows the order E=O<S<Se≪Te 18. Hence, the key goal of the present study is the preparation of a novel silanone under noble gas matrix isolation conditions.…”
Section: Methodsmentioning
confidence: 89%
“…The potential energy surfaces of dialkylsilanechalcogenone complexes (15; Ch = O, S, Se, Te) were theoretically studied for their formation, as well as their addition and cycloaddition chemistry. 12 The reactivity was shown to increase in conjunction an increase in principle quantum number of the Group 16 element.…”
Section: Group 14/16 Chemistrymentioning
confidence: 98%